On the advisability of long-term use of low-dose glucocorticoids in elderly patients with rheumatoid arthritis - A. V. Gordeev; E. V. Matyanova; E. G. Zotkin; A. M. Lila (Современная ревматология)
In managing elderly patients with rheumatoid arthritis (RA), it is essential to maintain a balance between treatment efficacy and safety, particularly concerning the use of glucocorticoids (GCs). Despite decades of GC use in comprehensive RA therapy, questions regarding the optimal safe dose, treatment duration, and the necessity of discontinuation or complete avoidance of these drugs remain unresolved.Objective: to assess the efficacy and safety of long-term low-dose GC use in elderly RA patients based on real-world clinical data.Material and methods. A retrospective cross-sectional analysis was conducted on 967 patients with active RA (ACR/EULAR, 2010) hospitalized in a specialized rheumatology center, who were non-responders to conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) and required initiation/resumption/switch of biologic DMARDs (bDMARDs) or targeted synthetic DMARDs. From the total sample, patients who had been receiving oral GCs for ≥6 months were selected (n=658). Group A (n=385) included young and middle-aged patients (18–59 years), and Group B (n=225) included elderly patients (≥60 years). Clinical and laboratory disease activity, extra-articular manifestations, severity and progression of RA, and pharmacotherapy features were assessed in all patients. Comorbidities were evaluated in all patients using the Cumulative Illness Rating Scale (CIRS).Results and discussion. The median duration of continuous GC use in elderly RA patients was 43 [13.5; 125] months, with a mean daily dose of 6.2±3.3 mg. The duration of GC therapy positively correlated with the time from arthritis onset to initiation of bDMARDs. Despite comparable inflammatory activity indicators (DAS28, SDAI, CDAI, etc.), RA in elderly patients was characterized by significantly longer disease duration (p<0.0001), greater severity, higher frequency of rheumatoid factor positivity and extra-articular manifestations of RA (p=0.0006), more frequent joint surgeries (p<0.0001), including total joint replacement (p=0.0009) and small joint arthroplasty (p=0.003). Compared to younger patients, elderly RA patients had significantly higher rates of comorbid conditions: coronary artery disease (p<0.0001), myocardial infarction (p=0.03), cerebrovascular disease (p=0.0003), polyneuropathy (p=0.004), chronic gastritis (p=0.002), interstitial lung disease (p<0.0001), chronic kidney disease (p<0.0001), type 2 diabetes mellitus (p=0.006), cataracts (p<0.0001), obesity (p<0.0001), and osteoporosis (p<0.0001), which resulted in a significantly higher CIRS multimorbidity index (p<0.0001).Conclusion. Long-term use of low-dose GCs in elderly RA patients was not associated with improved disease control in terms of disease activity or radiographic progression, nor with rational use of csDMARDs. It significantly delayed the timely initiation of bDMARDs and contributed to increased multimorbidity burden overall.